Delineation of groundwater potential zones using integrated vertical electrical sounding and geospatial techniques in the basement complex of Ijesha Isu Ekiti, Southwestern Nigeria - Taofeek O. Ewumi; Funmilola O. Ogunlana; Akintunde Akinola Oyedele (ITEGAM-JETIA)
A combination of multi-criteria evaluation parameters has been deployed to delineate groundwater potential zones using integrated Vertical Electrical Sounding and geospatial techniques in the basement complex of Ijesha Isu Ekiti, Southwestern Nigeria. The area is underlain by migmatite-gneiss, amphibolities, biotite gneiss and the granitic components of the basement complex terrain with suspect groundwater prospects.  Wenner vertical electrical soundings (VES) were conducted at 22 stations. The VES interpretation delineated the topsoil, weathered basement / partly weathered/fractured basement and the fresh basement bedrock with resistivity values ranging from 19 - 304, 16 - 417 and 8 - 2784 Ω-m, respectively. Integration of the attributes of the bedrock resistivity, weathered basement resistivity and the overburden thickness in a GIS environment enabled the classification of the study area into very low, low, medium and high groundwater potential zones covering areal extent of 0.004 km2, 0.18 km2, 1.85 km2, and 1.32 km2, respectively. A weighted combination of attributes would enhance the hitherto low success rate of groundwater targeting in a typical hard rock terrain.